INTERVENSI KEADILAN DAN ENGAGEMENT TERHADAP KEPEMIMPINAN DALAM MENINGKATKAN KOMITMEN ORGANISASIONAL KARYAWAN PERUSAHAAN DI JABODETABEK - Sopyan Mulyana (Jurnal Manajemen, 2019)
This research aims is to investigate the effects of transformational leadership, organizational justice, employee engagement toward organizational commitment. The background of this research based on the Gallup’s survey 2017 which reported that Indonesian’s employees who were engaged to their job and companies at the low level of 15% compare to four Southeast Asian countries: Malaysia 17%, Singapore 23%, Thailand 23%, and Philippines 36%. In response, to chase this lagging behind is required to conduct empirical studies to find the predictors that have significant effect toward employee engagement particularly in the Indonesian context. Due to the population is too broad hence this research is limited by area of Jakarta, Bogor, Depok, Tanggerang and Bekasi (JABODETABEK). The data was collected by questionnaire method through online survey with snowball sampling technique. The survey was responded by 188 repondents from various industries and position levels, which then selected only 128 respondents who qualified for this research are non-Board of Director and working in JABODETABEK area. This research apply path analysis technique and the data was processed using macro process SPSS by Andrew F. Hayes which aims to investigate the direct and indirect effects of the independent variables on the dependent through the mediators. The finding is transformational leadership has the indirect effect on organizational commitment through organizational justice and employee engagement, both alone or in serial, and organizational justice found has the strongest mediation effect on non-serial mediation.